2020
DOI: 10.1088/1361-6528/abb974
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of silicon nitride deposited by very high frequency (162 MHz)-plasma enhanced atomic layer deposition using bis(diethylamino)silane

Abstract: Silicon nitrides, deposited by capacitively coupled plasma (CCP)-type plasma enhanced atomic layer deposition (PEALD), are generally applied to today’s nanoscale semiconductor devices, and are currently being investigated in terms of their potential applications in the context of flexible displays, etc. During the PEALD process, 13.56 MHz rf power is generally employed for the generation of reactive gas plasma. In this study, the effects of a higher plasma generation frequency of 162 MHz on both plasma and sil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 29 publications
(32 reference statements)
1
10
0
Order By: Relevance
“…With the aim of optimizing the deposition process towards high-quality SiN x, we investigated the two separate half-reactions of the spatial ALD process with particular focus on the N 2 plasma exposure since it is has been reported that the plasma exposure can have dramatic influence on the impurity levels of SiN x prepared by PE-ALD [8,9]. Figures 4a and 4b show the saturation curves for SiN x grown from BDEAS and N 2 plasma at 200 o C and 250 o C. The GPC as a function of the BDEAS partial pressure, p, shows saturating behavior for SiN x , indicating self-limiting surface reactions during the precursor step, consistent with ALD behavior and with previous literature on temporal ALD [8,10]. The rotation speed was kept fixed at 20 RPM to fix the plasma exposure time, while the Ar bubbling flow through the BDEAS precursor was varied from 25 sccm to 150 sccm.…”
Section: Effect Of Plasma Exposure On the Materials Propertiessupporting
confidence: 86%
See 2 more Smart Citations
“…With the aim of optimizing the deposition process towards high-quality SiN x, we investigated the two separate half-reactions of the spatial ALD process with particular focus on the N 2 plasma exposure since it is has been reported that the plasma exposure can have dramatic influence on the impurity levels of SiN x prepared by PE-ALD [8,9]. Figures 4a and 4b show the saturation curves for SiN x grown from BDEAS and N 2 plasma at 200 o C and 250 o C. The GPC as a function of the BDEAS partial pressure, p, shows saturating behavior for SiN x , indicating self-limiting surface reactions during the precursor step, consistent with ALD behavior and with previous literature on temporal ALD [8,10]. The rotation speed was kept fixed at 20 RPM to fix the plasma exposure time, while the Ar bubbling flow through the BDEAS precursor was varied from 25 sccm to 150 sccm.…”
Section: Effect Of Plasma Exposure On the Materials Propertiessupporting
confidence: 86%
“…With atmospheric-pressure spatial ALD one can grow films with oxygen contents comparable to low-pressure temporal ALD. The carbon content is even lower than that reported for films grown from BDEAS and high-frequency Capacitively Coupled N 2 plasma (CCP) in low-pressure temporal PE-ALD, [10] and comparable to the films grown from bis(tert-butyl)aminosilane (BTBAS) in combination with N 2 plasma, yet much higher than those obtained by di(sec-butyl)aminosilane (DSBAS) and TSA in combination with N 2 plasma.…”
Section: Comparison To Pe-ald and Pe-cvdmentioning
confidence: 63%
See 1 more Smart Citation
“…Although the researches on SiN x PEALD using aminosilane precursors were heavily carried out, problems still remain to be studied and the biggest challenge in the PEALD process using aminosilane with N 2 plasma is known to be film conformality. , In addition, in the research studies on the SiN x PEALD process using aminosilane precursors and capacitively coupled plasma (CCP) for nitrogen reactant at high operating pressures, the radio frequency of 13.56 MHz has generally been used for the operation of plasma. ,,, However, for CCP, with increasing the operating frequency, the plasma density increases, whereas the ion bombardment energy to substrate decreases, which can improve the physical and electrical properties of PEALD thin films with reduced plasma damage. , Especially, very high frequency (VHF) plasma that can dissociate N 2 molecule effectively than conventional high frequency (HF) plasma is useful for the SiN x PEALD process requiring low hydrogen contamination by using N 2 plasma. We previously found that high quality SiN x thin films can be deposited effectively by VHF (162 MHz)-CCP PEALD using di­(isopropylamino)­silane (DIPAS) and N 2 plasma at a low process temperature (100 °C) …”
Section: Introductionmentioning
confidence: 99%
“…External bias is a method of applying additional bias to the main plasma; the plasma can be controlled by applying an RF source with different frequency, DC (negative or positive) or AC biasing. [18][19][20][21][22] Research of substrate negative biasing on PEALD is published by H. B. Profijt and Kessel. 20 According to this experimental result, the self-bias voltage generated by RF electric field applied to the substrate increases with RF power, and the energy of ions impinged during the PEALD process on the growing film increases and the characteristic of deposited thin film is changed; this is called the ioninduced effect.…”
mentioning
confidence: 99%